Analysis of shorting pin loaded half disk patch antenna for wideband operation - Ansari J.A.; Singh P.; Yadav N.P.; Vishvakarma B.R. (My University, 2025)
In the present paper the analysis of notch loaded shorted half disk patch is given. It is found that the bandwidth of the antenna depends inversely on the notch width whereas it is invariant with the notch length. Further, the antenna shows dual band behavior for a gap spacing below 7.5 mm in the gap coupled half disk shorted patch whereas it behaves as a wideband antenna for gap spacing more than 7.5 mm. Theoretical results are compared with simulated and experimental results. © 2009, Electromagnetics Academy. All rights reserved.